Clinical utility of thoracoscopy in elderly tuberculous pleurisy patients under local anesthesia. Issue 1 (January 2021) - Fujimoto, Shota; Saito, Keisuke; Matsubayashi, Sachi; Sato, Akihito; Yamada, Masami; Yamanaka, Yumie; Fujisaki, Ikumi; Odashima, Kyuto; Seki, Aya; Kazuyori, Taisuke; Seki, Yoshitaka; Takeda, Hiroshi; et al.
Abstract: Introduction: Diagnosing tuberculous pleurisy is important in Japan because it currently has a moderate tuberculosis prevalence. However, physicians often have difficulty making a diagnosis. It was reported that thoracoscopy under local anesthesia is useful for the diagnosis of tuberculous pleurisy, but there are no reports focusing on elderly patients. Methods: In this study, the usefulness of thoracoscopy under local anesthesia was evaluated in elderly patients. Among 170 patients who underwent thoracoscopy under local anesthesia at our hospital during 11 years from January 2008 to December 2018, those aged 75 years or older ( n  = 75) were investigated retrospectively. Results: A total of 55 patients underwent thoracoscopy under local anesthesia for detailed examination of pleural effusion of unknown cause. Of these, 18 were diagnosed as tuberculous pleurisy. The median age was 82 years (range: 75–92 years). The diagnosis of tuberculous pleurisy was made in 11 patients in whom Mycobacterium tuberculosis was detected and in four patients whose pathological findings indicated epithelioid granuloma accompanied by caseous necrosis. Clinical diagnosis was made in the remaining three patients based on thoracoscopic findings of the pleural cavity and a high level of adenosine deaminase in pleural fluid. No serious complications attributable to the examination were observed in any patient. Conclusions: Thoracoscopy under local anesthesia was useful for the diagnosis of tuberculous pleurisy in elderly patients, with useful information being also obtained for the treatment of tuberculosis.